PENGARUH KOMPENTENSI APARATUR PEMERINTAH DESA, PARTISIPASI PENGGUNAAN, USABILITY SISTEM TERHADAP EFEKTIFITAS PENERAPAN SISTEM KEUANGAN DESA (SISKEUDES) PADA DESA-DESA SE KECAMATAN MAUROLE - Rega, Yohanes Don Bosko; Thalib, Sabra B Wahab; Sayang, Sabulon (Program Studi Akuntansi Universitas Flores, 2023)
This research aims to determine the influence of village government apparatus competency, usage participation, system usability on the effectiveness of implementing the village financial system (Siskeudes) in villages throughout Maurole District. This research is a type of quantitative research. The sampling technique used purposive sampling, totaling 30 respondents. The data analysis techniques used are Descriptive Statistics, Data Quality Test, Classical Assumption Test, Multiple Regression Analysis, and Hypothesis Testing. The results of this research show that: (1) Village Government Apparatus Competence has a significant positive effect on the Effectiveness of Implementing the Village Financial System (Siskeudes) in Villages in Maurole District, this is proven by the test results which show the regression coefficient value for the Village Government Apparatus Competence variable is equal to 0.452 with a calculated t value of 3.055 > 2,056 and a significance level of 0.005 <0.05. (2) User Participation has no effect on the Effectiveness of the Implementation of the Village Financial System (Siskeudes) in Villages in Maurole District, this is proven by the test results which show the regression coefficient value for the User Participation variable is 0.112 with a calculated t value of 0.598 < 2,056 and a significant level 0.555 > 0.05. (3) System Usability has a significant positive effect on the Effectiveness of the Implementation of the Village Financial System (Siskeudes) in Villages in Maurole District, this is proven by the test results which show the regression coefficient value of the Usability System variable of 0.446 with a calculated t value of 2.758 > 2,056 and the level significant 0.011<0.05. Based on the results of the determinant coefficient test (R2), it shows that the percentage contribution of the independent variable (Village Government Apparatus Competence, Usage Participation, System Usability) to the dependent variable (Effectiveness of Implementing the Village Financial System (Siskeudes) is 41.1% and the remaining is 58.9%. % influenced by variables outside the model that are not explained.